Optical properties of ZnO fabricated by hydrothermal and sonochemical synthesis - Zakirov, M I; Kuryliuk, V V; Korotchenkov, O A (Journal of physics. Conference series, 2016)
This paper presents the results of experimental study of photoluminescence (PL) and surface photovoltage of ZnO synthesized in this study. Two types of zinc oxide samples, prepared by hydrothermal and sonochemical methods at two different temperatures, are contrasted. The observed differences in their PL spectra are associated with different mechanisms of formation and resulting concentration of point defects. At a high-temperature synthesis, blue luminescence band prevails. Reducing the temperature causes the increase in intensity of the yellow-red luminescence band.